Esham, the Origin of Sukuk for Facing the Crisis: Historical Experience - Khairunnisa Musari (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2021)
Pandemic brings a crisis. This makes world leaders have to work hard and smartly in managing state budgets. During the heyday of Islam, Muslims also faced crises. Given that time the power of Islam mastered many areas of the world, it can be assumed that the crisis that occurred in the past was a global crisis as it is happening today. The difference is the crisis that occurred at the time because of losing the war. This paper tries to describe the historical experience of the esham, one of the fiscal instruments in the Islamic world that helped the Ottoman Empire overcome the crisis. Esham has mobilized low-cost funds from the public in a relatively concise time. Esham served as a better choice than looking for foreign debt. As the origin of sukuk, esham has simpler structure so that can be used as an alternative to sukuk with a lower cost. To deal with a crisis, esham may intervene in the economy. Esham funds to the real sector in turn will help the government drive the economy as well as control prices in the market for goods and services. Therefore, esham has the potential in facing the crisis.